THE NATIONAL SCIENCE FOUNDATION SUMMER INSTITUTE PROGRAM. - Smalheer, Carol J. (Science Education, 1964)
The article reports on the establishment of the National Science Foundation (NSF) in 1950, which was commissioned to find new ways to employ the resources of the Federal Government to strengthen education in all the fields of science in the U.S. The Summer Science Institutes, which have been geared to encourage high-ability secondary school students to pursue their scientific interests, are supported as one of many programs to advance the standards of the NSF. The programs in the area provide research participation experiences in which students work along side experienced scientific investigators to obtain first-hand knowledge.